URGENSI KRITERIA POLITIK UANG DALAM PERATURAN PERUNDANG- UNDANGAN ATAS PELAKSANAAN KAMPANYE MENJELANG PEMILIHAN UMUM - Nur Hidayah Hasibuan; M. Iraqi Fauzi, Deo Agung Haganta, Putri Amellia Simbolon, Unedo Sinaga, Ramsul Nababan (Jurnal Salome : Multidisipliner Keilmuan, 2023)
The practice of money politics is included in electoral criminal offenses, including in the regional elections. This crime often occurs but is difficult to process. This is due to the obstacles faced by Bawaslu in carrying out the handling, namely the absence of criminal sanctions norms, the limited authority of Bawaslu and differences in perceptions at the Gakkumdu Center. For this reason, efforts that must be made in the regional elections are to revise the law and give Bawaslu full authority in handling election criminal violations, including the practice of money politics. It is hoped that the results of this study will provide a better understanding of money politics in legislative regulations in general elections. The findings and recommendations from this research can be the basis for more effective policy making in preventing and dealing with political money in general elections in Indonesia.